2023
DOI: 10.3390/molecules28073272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Application Potential of a Recombinant Ganoderma Protein as Bioactive Ingredients in Cosmetics

Abstract: The aim of this study was to evaluate the application potential of a recombinant fungal immunomodulatory protein from Ganoderma lucidum (rFIP-glu). First, a recombinant plasmid pPIC9K::FIP-glu-His was transferred into Pichia pastoris for the production of protein. The protein was then to assess its free radical scavenging abilities and the effect on the viability of both human immortalized keratinocytes (HaCaT cells) and mouse B16-F10 melanoma cells (B16 cells) in vitro, followed by the effect on the melanin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The ATR-FTIR spectra of the surface layers cut off from the stipe and the abhymenial side of pilei from dried basidiocarps of G. applanatum 2023 (1) and G. resinaceum (7) are shown in Figures 6a and 7a, respectively. Despite some weak protein features, the spectra measured for strain 1 represent the purest triterpenoid bands among all basidiocarp samples measured in this study, and even weak skeletal vibration bands of these compounds are visible below 900 cm −1 .…”
Section: Triterpenoid Distribution In Ganoderma Basidiocarpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ATR-FTIR spectra of the surface layers cut off from the stipe and the abhymenial side of pilei from dried basidiocarps of G. applanatum 2023 (1) and G. resinaceum (7) are shown in Figures 6a and 7a, respectively. Despite some weak protein features, the spectra measured for strain 1 represent the purest triterpenoid bands among all basidiocarp samples measured in this study, and even weak skeletal vibration bands of these compounds are visible below 900 cm −1 .…”
Section: Triterpenoid Distribution In Ganoderma Basidiocarpsmentioning
confidence: 99%
“…Fungi of this genus contain proteins, polysaccharides, triterpenoids, polyphenols, and other substances with various biological effects [1][2][3], so they can be used in functional foods [4], pharmacy [5], or cosmetics [6]. The genus Ganoderma demonstrates a wide variety of species and strains, differing in genetics, morphology, and biochemical composition [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…the anti-inflammatory efficacy of HaCaT cells by detecting the expression of inflammatory factors IL-6, TNF-a and COX-2. The results showed that the fermentation broth of Xanthopanax has a great potential to be used in cosmetics as an efficacious raw material for anti-aging, anti-inflammatory and antioxidant applications Guo et al (2023). assessed the potential application of recombinant Ganoderma lucidum protein (rFIPglu) as a bioactive ingredient in cosmetics, then the protein was evaluated for its free radical scavenging ability and its effect on the in vitro viability of human immortalised keratinocytes and mouse B16-F10 melanoma cells, and then on the melanin synthesis of the B16 cells.…”
mentioning
confidence: 99%